The Silent World of Sudden Onset Sensorineural Hearing Loss Treatment with Volume Expanders and Intravenous Steroid: 5 Years Experience - Abdul Rashid, Khairul Naimah; Noh, Khairul Bariah; Amir, Saidatul Akmaliah; Zulkefli, Nor Syazwani; Salim, Rosdan (International Journal of Human and Health Sciences (IJHHS), 2024)
Objectives: Sudden onset sensorineural hearing loss is one of the ORL emergencies causing the patient's fear of the risk of permanent hearing loss if not intervened promptly. This study aims to determine the efficacy of volume expanders and intravenous dexamethasone in the treatment of sudden onset sensorineural hearing loss. Methods: We conducted a retrospective study of patients presented to our tertiary centre from January 2015 until June 2023. A total of 62 patients with sudden onset hearing loss of more than 30dB in three consecutive hearing levels. The patient’s age, co-morbids, disease history, the severity of hearing loss and the onset of treatment were studied to correlate with the patient’s recovery. Treatment protocol with a volume expander (Tetraspan) and intravenous dexamethasone was followed. Audiogram pretreatment and post-treatment were analysed. Results: Improvement in overall audiogram level was seen in 31 patients (50%) who received volume expander and intravenous dexamethasone. Early intervention in patients who presented with a history of hearing loss of less than 4 days showed 90% improvement in audiogram. Patients without chronic medical diseases such as diabetes mellitus, hypertension, chronic kidney disease and dyslipidemia showed 78% improvement in audiogram irrespective of onset of treatment. Conclusion: Early detection and intervention with volume expander and intravenous dexamethasone overall help in hearing recovery in patients with sudden onset sensorineural hearing loss. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S40